2021
DOI: 10.5194/aab-64-387-2021
|View full text |Cite
|
Sign up to set email alerts
|

Crude glycerin is an efficient alternative to corn in the diet of feedlot lambs

Abstract: Abstract. The objective of this study was to evaluate the intake, digestibility, nitrogen balance, and performance of feedlot lambs fed diets containing crude glycerin. A total of 30 Ile de France lambs were confined to individual pens at an average age of 45 d: 15.1 kg initial body weight and 32.2 kg final body weight. The animals were distributed in a completely randomized design and fed three diets containing fresh sugarcane as forage (50 %) and concentrate (50 %), with or without the inclusion of 100 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Other studies indicated that the effect of glycerol on the performance and productivity of cows depends on the level and purity of glycerol added to the feed (19,26,45). Despite those and other studies that indicated the importance and role of glycerol in enhancing cow productivity, they did not indicate the qccurate level of dietary glycerol (33). The aim of this study was to study the effect of adding different levels of dietary pure glycerol on the production and components of milk and some blood parameters.…”
Section: Introductionmentioning
confidence: 90%
“…Other studies indicated that the effect of glycerol on the performance and productivity of cows depends on the level and purity of glycerol added to the feed (19,26,45). Despite those and other studies that indicated the importance and role of glycerol in enhancing cow productivity, they did not indicate the qccurate level of dietary glycerol (33). The aim of this study was to study the effect of adding different levels of dietary pure glycerol on the production and components of milk and some blood parameters.…”
Section: Introductionmentioning
confidence: 90%
“…Among the products that have been most tested in this regard in recent years is glycerin. Several studies have investigated the effects of glycerol on production parameters in dairy cows [4], beef cattle [5], goats [6], and lambs [7]. However, studies on its effects on reproduction, especially in goats, remain scarce.…”
Section: Introductionmentioning
confidence: 99%